2023
DOI: 10.1111/gwao.12952
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating masculinities at the expense of health: A qualitative study on men working in long‐term care in the Netherlands, from an intersectional perspective

Abstract: While some areas of care work show increased recruitment of men, the care‐gap remains, especially in low paid occupations. Questions arise how masculinities play a part in this, and if caring masculinities obscure gender inequities while at the same time perpetuating them. This qualitative study focusses the negotiation of hegemonic and caring masculinities of men working in residential long‐term care in the Netherlands, and its consequences for health. Semi‐structured interviews (N = 16) were analyzed themati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
(66 reference statements)
2
11
0
Order By: Relevance
“…This is also supported in a study by van Wees et al. (2022), who found that racialized men had to work harder to be considered as competent care workers.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…This is also supported in a study by van Wees et al. (2022), who found that racialized men had to work harder to be considered as competent care workers.…”
Section: Introductionsupporting
confidence: 67%
“…Previous research suggests that this seems to be the case especially for Black men working in the care sector. This is also supported in a study by van Wees et al (2022), who found that racialized men had to work harder to be considered as competent care workers.…”
Section: Men In Women-dominated Occupationssupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, we included a diverse population that allowed us to understand inequities between self‐employed women in LTC. This study did not address the experiences of men working as self‐employed care workers, which were distinctly different and were thus described elsewhere (Wees et al, forthcoming) Our findings cannot be transferred to all care workers in LTC, as we explicitly aimed to pay attention to particular groups of self‐employed care workers that are currently overlooked in studies or policy papers. Our study aimed to explore experiences of low‐paid care workers, but our sample consisted for a large part of advanced nursing aides and nurses.…”
Section: Discussionmentioning
confidence: 88%
“…The consolidated criteria for reporting qualitative research (COREQ) guided the reporting of the study (Tong et al, 2007). Findings from other sub‐studies are published elsewhere (Duijs et al, 2021, , submitted; Wees et al, in press).…”
Section: The Studymentioning
confidence: 91%